Relasi Otoritas dan Tradisi dalam Pewacanaan Pancasila pada Tafsir Al-Azhar - Akmal Rizki Gunawan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
The Relations of Authority and Traditions in Pancasila Discourse on Tafsir Al-AzharRevealing the reasons and describing Hamka's interpretation behind his inconsistency and ambiguity towards Pancasila discourse in Tafsir Azhar and several of his works is the aim of this article. On one side, Hamka accepted Pancasila (1951), but on the other side, Hamka firmly rejected Pancasila (1957-1966). This paper will highlight the phenomenon above using the Maudhui Al-Farmawi method of interpretation and philosophical Hermeneutic Theory of Hans Georg Gadamer. This research proves that the existence of a relationship of authority and tradition encompassing Hamka has implications for inconsistencies (acceptance and rejection) in Pancasila discourse in his primary work Tafsir Al-Azhar and the other several secondary works. In this case, the writer concludes that Hamka, through authority and tradition, undergoes a formation and transformation within himself, so that he no longer tends to impose his objective and reflective attitudes on some of his subjects. However, he is also open-ended in a way that lets others speak differently, so that it has implications for the intersection and integration (fusion) horizons of understanding. Hamka Transformation in the context of Pancasila can be understood that Hamka is an idealistic figure in understanding the first principle of "God Almighty" and a compromise figure in understanding the second to the fifth precept.